The ERA-Related GTPase AtERG2 Associated with Mitochondria 18S RNA Is Essential for Early Embryo Development in Arabidopsis - Cheng, Pengyu; Li, Hongjuan; Yuan, Linlin; Li, Huiyong; Xi, Lele; Zhang, Junjie; Liu, Jin; Wang, Yingdian; Zhao, Heping; Zhao, Huixin; Han, Shengcheng (Frontiers in Plant Science, 2018)
The ERA (E. coli RAS-like protein)-related GTPase (ERG) is a nuclear-encoded GTPase with two conserved domains: a GTPase domain and a K Homology domain. ERG plays a vital role in early seed development in Antirrhinum majus. However, the mechanism that regulates seed development remains unclear. Blasting the genome sequence revealed two homologies of ERG, AtERG1, and AtERG2 in Arabidopsis. In this study, we found that AtERG2 is localised in the mitochondria and binds mitochondrial 18S RNA. Promoter and transcript analyses indicated that AtERG2 was mainly expressed in the leaf vein, trichome, and ovule. The T-DNA insertion lines of AtERG2 showed silique shortage, early seed abortion, and sporophytic maternal effects, in which some seeds arrested in the zygotic stage at 1.5 days after pollination (DAP) and aborted at 2.0 DAP in aterg2-1 +/-. We further showed that the ovules of these arrested seeds presented unusual tissue degradation inside the embryo sacs. Reactive oxygen species (ROS) accumulated at 1.0 and 1.5 DAP in the arrested seeds, and the transcription of several ROS-responsive genes, WRKY40, ANAC017, and AOX1a, was up-regulated in the aterg2-1 +/- arrested seeds at 1.5 and 2.0 DAP, but not in wild-type (WT) and aterg2-1 +/- developed seeds. The cell death-related gene BAG6 was also transcriptionally activated in aterg2-1 +/- seeds arrested at 2.0 DAP. Additionally, the protein level of mitochondria protein ATPase Subunit 6 was lower in 2-DAP siliques of aterg2-1 +/- than it was in those of WT. These results suggested that AtERG2 promotes early seed development by affecting the maturation of the mitochondria ribosome small subunit and mitochondrial protein translation in Arabidopsis.